Cycling near misses: Their frequency, impact, and prevention. (August 2016) - Aldred, Rachel
Highlights: The paper reports on a diary study of 1500 UK cyclists, which found 'very scary' incidents happen weekly. Different types of near miss are associated with different levels of injury risk, fear, and annoyance. Cyclists believed that while most near misses could be prevented, usually this was not within their control. Sharing with motor vehicles, especially large vehicles, seems problematic, with a 'might is right' road culture described. Segregated infrastructure, alongside interventions targeted at road culture and driver behaviour, is recommended. Abstract: This paper explores cyclists' experiences of non-injury incidents, arguing that these are important for cycling experience and uptake as well as for injury prevention. It discusses different types of non-injury incident collected in a recent survey of UK cyclists. These are everyday occurrences that in some cases have a substantially negative impact on cycling experiences. This article explores the impact of different incident types on people cycling both immediately and in the future. It analyses what near misses tell us about cyclists' experience of problems related to road user behaviour and culture, and infrastructural conditions for cycling. The paper explores what cyclists experiencing near misses think might have prevented them. Based on this and on a comparison with common types of injury incidents, summary recommendations are made for policy and future research.